The Effect of the Competitive Structure Upon Expenditures for Advertising - Simon, Julian L. (Quarterly Journal of Economics, 1967)
Introduction, 610. — Case 1: Firms whose response functions pass through the origin, 612. — Case 2: Firms whose response functions are positive at zero promotion levels, 619. — General discussion and conclusions, 626.